Prevalence of Dental Anomalies in Pediatric Patients visiting Tertiary Care Hospital: A Panoramic Radiograph based study - Adhikari, Sagar; Bali, Harleen; Kuikel, Ganga; Lakhemaru, Reena; Maharjan, Prakriti; Thapa, Richa; Bhattarai, Bina (Nepal Journal of Health Sciences, 2024)
Introduction: Dental anomalies are deviations from the normal development, structure, or appearance of teeth. These anomalies can affect the number, size, shape, position, and structure of teeth.Objective: This study aimed to assess the prevalence of dental anomalies in the pediatric patients visiting Kathmandu University School of Medical Sciences (KUSMS), Dhulikhel Hospital, Nepal.Methods: A descriptive cross-sectional study was conducted at KUSMS, Dhulikhel Hospital. The panoramic radiographs of the pediatric patients between 6 and 14 years of age in the archive of the hospital were assessed for the presence of dental anomalies.Results: Of the total 451 panoramic radiographs meeting the inclusion criteria, 55.9% were male and 44.1% were female. The overall prevalence of dental anomaly was 26.8 % with rotation as the most common anomaly (19.3%) followed by missing (6.7%), supernumerary teeth (4.4%), dilaceration 2.4 %, gemination (1.8%), dens-in-dente (1.1%) and peg shaped (0.9%).Conclusions: The most common dental anomaly among the pediatric patients was rotation followed by missing and supernumerary tooth.